1996
DOI: 10.1007/bf00127887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medium composition, pH and temperature on the growth and viability of Lactobacillus acidophilus

Abstract: The Lactobacillus acidophilus growth was investigated to find the optimal concentrations of 2 nitrogen sources (thought to be in excess) and 2 organic acids. A Plackett and Burman experimental design was used allowing identification of the more imlx)rtant factors with very few experiments. In the studied range, all the factors had a linear effect and a great influence on the final viability. 20 g/L of each nitrogen sources, 3 g sodium-citrate/L and 5 g sodium acetate/L are necessary, pH, temperature and glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Owing to the complexity of cereal substrates, the main compositional changes that were monitored to justify their fermentability were FAN and TRS. Research studies using semi‐defined synthetic media have identified these compounds as the most crucial factors for lactic acid bacteria growth (Taillandier et al. 1996; Loubiere et al.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the complexity of cereal substrates, the main compositional changes that were monitored to justify their fermentability were FAN and TRS. Research studies using semi‐defined synthetic media have identified these compounds as the most crucial factors for lactic acid bacteria growth (Taillandier et al. 1996; Loubiere et al.…”
Section: Discussionmentioning
confidence: 99%
“…acidophilus , the small increase in cell populations (1·21 ± 0·12 log 10 cfu ml −1 ) could be explained by the possible absence of specific nutrients in the malt medium, such as free amino acids, B‐vitamins or minerals. This species has complex growth requirements (Gomes and Malcata 1999), usually exhibiting poor growth in synthetic media without the addition of large amounts of supplements, such as yeast extract and peptone (Taillandier et al . 1996; Elli et al .…”
Section: Discussionmentioning
confidence: 99%
“…This result may be related to the optimal pH value for growth, which was pH 6 for Lb. acidophilus (Taillandier et al, 1996).…”
Section: Influence Of Fermentation Ph On the Cryotolerance Of Lb Acidophilus Rd758mentioning
confidence: 99%